The Trend of Governmental Support from Post-Graduated Ira¬nian Students in Medical Fields to Study Abroad - M Afshari; Z Rafiee; M Ghazi; AA Haghdoost (Tehran University of Medical Sciences, 2013)
Background: To explore the trend and composition of post-graduate Iranian students who received governmental scholarship during the last two decades.Method: Detailed information about the awarded scholarships and also about the number of post graduate students in clinical and basic sciences in domestic universities were collected from the related offices within the ministry of health and medical education and their trends were triangulated.Results: A sharp drop was observed in the number of awarded scholarships, from 263 in 1992 to 46 in 2009. In the beginning, almost all of scholarships fully supported students for a whole academic course; while in recent years most of scholarships supported students for a short fellowship or complementary course (more than 80%). Students studied in a wide range of colleges within 30 countries; more than 50% in Europe. Although one third of students studied in UK in the first years, only 4% of students selected this country in recent years. conversely, the number of scholarships to Germany and sweden have increased more than 10 and 3 times during this period. In parallel, the capacity of domestic universities for training of post-graduate students has been expanded dramatically.Conclusion: Although expanding post-graduate education has been one of the main strategic objectives of the ministry of health and medical education in last two decades, it was obtained using different approaches. By time, more attention was to expanding the capacities of Iranian universities, and choosing less but more targeted students to continue their studies abroad.